PENGARUH BIAYA KEAGENAN DAN KESEMPATAN INVESTASI TERHADAP KEBIJAKAN DIVIDEN (Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia) - Widarni, Eny Lestari (DINAMIKA DOTCOM, 2011)
Target of this research is to determine relation among expense of agent, and opportunity of invesment with policy of dividend related to policy of dividend and expected by this research can give contribution to science in the field of accountancy, specially variables related to ratio payout dividend. Population in this research is all noted company at index of LQ-45 in Stock Exchange Indonesia, used by analysis is regresi. Result of research is the expense of agent do not have an effect on to policy of dividend, while opportunity of invesment give influence to policy of dividend.Â Keyword : expense of agent, opportunity of invesment and policy of dividend